A failure to engage? Negotiating the gap between students' expectations and tutors' assumptions in seminars. (1st January 2023) - Jones, Sophie H.
Abstract : Seminar-based teaching remains of continued importance to many degree programmes, particularly within the author's discipline of the humanities and social sciences. However, one of the perennial concerns cited by practitioners in Higher Education (HE) relates to engaging students in seminars. In contrast to earlier works which are concerned solely with techniques to better engage students within the classroom, through the use of a literature review, this paper explores deeper the expectations about teaching and learning that students bring with them to HE, as well as the assumptions that teachers in HE make about their students when planning teaching and learning activities. Ultimately it concludes that tutors must do more to understand their students' experiences in transitioning to university, particularly for first-generation students, and work with students to negotiate new styles of teaching and learning which will be unfamiliar to many of them. This article was published open access under a CC BY licence: https://creativecommons.org/licences/by/4.0 .